Implementasi Green School Melalaui Edukasi Kimia Lingkungan Di Tingkat SMA Di Kecamatan Bangkinang Kota - Kasman Ediputra; Adityawarman Hidayat; Etika Yusrina (EL-EMIR INSTITUTE, 2026)
The increasing environmental damage caused by human activities demands education that can shape environmentally conscious character from school age. One strategy that can be implemented is the implementation of Green School through environmental chemistry education. This study aims to analyze the implementation of Green School through environmental chemistry learning at the high school level in Bangkinang Kota District and identify its relationship with students' environmental behavior. The study used a quantitative descriptive approach with a survey method of 120 grade XI MIPA students from three high schools selected using proportional random sampling. Data were collected through questionnaires, observations, and interviews, then analyzed using descriptive statistics and Pearson correlation tests. The results showed that environmental awareness achieved the highest score (85.1), followed by Green School implementation (83.7), environmental knowledge (82.5), and environmentally friendly behavior (80.3). The greening program, waste management, and environment-based learning have been running well. The correlation analysis showed a strong positive relationship between environmental chemistry education and Green School implementation (r = 0.742; p < 0.05), thus improving environmental literacy, shaping environmental awareness, and strengthening a sustainable school culture